2011
DOI: 10.1016/j.epidem.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school holidays on the social mixing patterns of school children

Abstract: School holidays are recognised to be of great epidemiological importance for a wide range of infectious diseases; this is postulated to be because the social mixing patterns of school children - a key population group - change significantly during the holiday period. However, there is little direct quantitative evidence to confirm this belief. Here, we present the results of a prospective survey designed to provide a detailed comparison of social mixing patterns of school children during school terms and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 23 publications
5
68
0
1
Order By: Relevance
“…The decline in incidence is coincident with Christmas holidays, and the resurgence of cases in this age group in the new year, after schools had reopened, is similar to other data [7,19-21]. The observation that incidence in the 19-45 year olds lagged behind the youngest age group, suggests that under 18s may have brought the illness back to their families.…”
Section: Discussionsupporting
confidence: 87%
“…The decline in incidence is coincident with Christmas holidays, and the resurgence of cases in this age group in the new year, after schools had reopened, is similar to other data [7,19-21]. The observation that incidence in the 19-45 year olds lagged behind the youngest age group, suggests that under 18s may have brought the illness back to their families.…”
Section: Discussionsupporting
confidence: 87%
“…Contact studies have found that school closures reduce contact between children substantially but have much less effect on adults' contact behaviour [51], [63], [64]. In a UK study, children's contacts were reduced overall during school holidays, but the number of contacts they made with adults increased [62]. The assumptions made in the modelling studies were therefore generally consistent with empirical data, but incorporating additional contact data into transmission models, as they become available, may increase the reliability of model predictions.…”
Section: Discussionmentioning
confidence: 95%
“…For example, it has been estimated that if such contacts increased 1·5 times more during a pandemic closure than during school holidays, then the benefits of school closure would be minimal [13]. This limitation arises partly because there are relatively few data regarding the effects of school closures, particularly reactive closures, on contact patterns [51], [52], [62][65] (although several studies estimated the effects of school closures on contact patterns using either empirical data or modelling techniques [13][17]). Existing data typically refer to face-to-face conversational contacts, which appear to be a good proxy for transmission of respiratory infections including influenza [66], although further studies are needed of the precise nature of contacts which are sufficient to allow transmission [67].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the daily number of age-dependent contacts for children can vary between term-time and holidays or weekends [42][43][44]. The inclusion of additional contact matrices in the model would improve the accuracy of the mathematical model in estimating the daily number of contacts sufficient for influenza transmission between children and their contacts.…”
Section: Study Limitationsmentioning
confidence: 98%